Accelerated and outdoor weathering of silver nanowire transparent conductors under electrical stress in pseudo-modules. (18th January 2022) - Chang, Hung-Shuo; Feng, Pan; Lyu, Yadong; Lin, Chiao-Chi
Abstract: In realistic applications, silver nanowires (AgNWs) are encapsulated in optoelectrical devices to function as transparent conductors and electrodes. Environmental stressors along with the essential electrical stress are inevitably harmful to the AgNWs inside the devices. Herein, to investigate the degradation behavior discrepancy between materials-level and device-level tests, we adopted pseudo-module to mimic the encapsulation. The pseudo-module allows the application of electrical stress and facilitates the interim specimen access for materials characterization through assembly-disassembly. Indoor accelerated and outdoor weathering tests with applied electrical stress to the pseudo-module encapsulated AgNW networks were performed. The impaired optoelectrical properties and morphological changes of AgNWs due to multiple or individual stressor(s) are investigated. Results indicate UVA exposure at elevated temperature coupled with electrical stress is responsible for the electrical failure of AgNW networks. Sulfidation that depresses optical transparency of AgNW networks is prone to occur at lower temperature. This work provides unambiguous degradation behaviors of AgNWs inside encapsulants, helping to improve the design of AgNWs related optoelectrical devices in the applications of solar irradiation environments.